Auditoría de gestión al colegio experimental “Pio Jaramillo Alvarado” de la ciudad de loja período 2012” - Matailo Yaguana, Luisa María (2016)
This research work entitled " AUDIT MANAGEMENT TO SCHOOL EXPERIMENTAL " PIO JARAMILLO ALVARADO " Loja CITY YEAR 2012" . It was developed in accordance with the General Standards for graduation at the National University of Loja as a pre opt Engineer Degree in Accounting and Auditing Carrera requirement. Worth noting that developed an issue of vital importance , fulfilling the objectives were designed to perform Auditing the Experimental College " Pio Jaramillo Alvarado " evaluate the internal control implemented in the institution, in terms of their resources to determine the degree of reliability; questionnaire through the internal control weaknesses were noted school , to evaluate compliance with the laws and regulations of the organization and provide recommendations to help the improvement and strengthening of the school , verify compliance with administrative activities , allowing to determine the weaknesses in each component to review, by management Audit process , applying indicators to measure efficiency , effectiveness and quality in achieving institutional goals and objectives to determine the degree of management of each of the components , prepare a report to the Audit Management Experimental College " Pio Jaramillo Alvarado " containing opinions , conclusions and recommendations to their managers to make informed decisions and meet corporate objectives. The methodology used was to inquire at school under study, to apply concepts, techniques and regulations governing the operation of the school, which helped us to develop it, then the previous visit was made to the institution for the collection source information and proceed to initiate the audit , conducting planning , detailing the audit programs and questionnaires of internal control, for the components examined, which allowed the analysis of them and select the most relevant findings through implementation of audit testing whether compliance or substantive , which were supported in the working papers , which were subsequently presented in the reporting of results for future decision -making. The results of the study helped identify shortcomings as incompatible activities done their job , lack of an existing manual functions , since from years ago has been working with outdated rules , on the other hand is not done the pre - numbering of the trades that allow ready determination, in the teaching area has been neglected aspect of training teachers and likewise some teachers lack professional title according to its functions causing the knowledge imparted those required by the Ministry of Education and Culture. The main specific findings in the audit of management on can be set in the Experimental College " Pio Jaramillo Alvarado " has not been subject to evaluations by Audits and Financial Management , the Internal Control System has implemented the Experimental College " Pio Jaramillo Alvarado " has some flaws that must be corrected , the same as detailed in the accompanying audit report and within the faculty , do not have the title of teacher requiring manual positions of the institution and lack of continuous training to them , limiting the ability to be consistent with science and technology to perform the functions performed according to their specialty. In contrast to these findings it is recommended that the highest authority of the Association to consider the recommendations of the report of this audit and define corrective to improve the control system and thus allow you to have a high level of confidence.